Thermal Plasma Spheroidization and Characterization of Stainless Steel Powders Using Direct Current Plasma Technology - Pierpaolo Iovane; Carmela Borriello; Giuseppe Pandolfi; Sabrina Portofino; Gabriella Rametta; Loredana Tammaro; Nicola Fedele; Sergio Galvagno (Plasma, 2024)
The production of spherical powders has recently registered a boost due to the need to fabricate new printing materials for Additive Manufacturing applications, from polymers and resins to metals and ceramics. Among these materials, stainless steels powders play a leading role, since they are widely used in industry and everyday life; indeed, micron-sized spherical stainless steel powders have specific characteristics and are considered as one of the best candidates for Additive Manufacturing systems and for application in a wide range of sectors. In this paper, stainless steel 316 L powders were used to explore and identify the best process parameters of a thermal plasma process able to produce spherical powders for Additive Manufacturing applications. X-ray Diffraction, Scanning Electron Microscopy, Particle Size Distribution and Flowability analysis were performed to characterize reagents and products. Powders with a high circularity (>0.8) and improved flowability (<30 s/50 g) were successfully obtained. The collected results were compared with data available from the literature to identify the potential use of the spherical produced powders.